Political persuasion and use of humor on social media: The case of Turkish Youth - Nazlı Aytuna,; Çapraz, Yeşim Ceren (Technium Social Sciences Journal, 2021)
While social media is creating a new ground for political debate, humor also appears as a creative tool for this new political communication language. The present study aims to investigate the use of humor on social media as a means of political persuasion based on a qualitative survey on the Turkish young generation. The present research is based on 64 semi-structured interviews conducted on Turkish young citizens. As a result, in the first place, it presumes that the convergence of humor on social media provides a possible counterforce to the digital evidence that allows disinterested users to avoid political information. Secondly, the present study shows also that humor on social media facilitates exposure to diverse political perspectives and becomes an effective persuasion instrument of political communication.